Science student teachers'views about their competency in teaching - Hava Ipek,; Atilla Cimer,; Salih Cepni, (penerbit ukm, 2011)
The purpose of this was to determine student teachers' view of professional development and lifelong learning and how much do they feel themselves prepared for being professional as a teacher. The study was carried out with 25 science student teachers in Fatih Faculty of Education at Karadeniz Technical University in Trabzon. A survey research design with six open-ended questions was employed as a research method. Qualitative and quantitative data were gathered.Findings of the research showed that science student teachers insufficient in classroom felt the are control.subject knowledge. However,competent in, professional and pedagogical issues. In implication of that, more emphasis should be given to practical activities, the alttainment level of content knowledge taught in subject courses should be appropriate to primary school level, and the attainment ways to knowledge should be taught.